Effects of ‘Candidatus’ Liberibacter Asiaticus on the Root System of Poncirus trifoliata Hybrids as a Rootstock for ‘Valencia’ Scion - Cavichioli, Thaís Magni [UNESP]; Curtolo, Maiara; Cristofani-Yaly, Mariangela; Rodrigues, Josiane; Coletta-Filho, Helvécio Della (MDPI, 2024)
The symptoms of huanglongbing (HLB), a disease caused by the bacterium Candidatus Liberibacter asiaticus (CLas), are visible on the canopy of citrus plants. They include mottling of leaves followed by dropping and lopsided fruits with premature dropping. Loss in phloem functionality and degradation of the root system are also HLB symptoms with a severe impact on plant growth and production. Some Citrus relatives, such as Poncirus trifoliata and its hybrids, have shown more tolerance to HLB disease and low titers of CLas compared to Citrus species, but little is known about the effects of CLas on their root system. In this study, we investigated the effects of CLas-infected ‘Valencia’ scion on the citrandarin IAC3222 (a hybrid between P. trifoliata and Sunki mandarin) used as rootstock as well as interstock between ‘Valencia’ and Swingle citrumelo rootstock. At 13 months post-inoculation, the cycle threshold values (CT) for CLas in the infected scion samples indicated a high CLas titer (from 15.9 to 22.7) regardless of the rootstock variety or interstock used. However, no CLas-positive samples were detected in the roots of IAC3222 (CT ranging from 37.9 to 40.0), in contrast to all Swingle roots (CT ranging from 27.9 to 31.3). Both root volume and mass were reduced in IAC3222 compared to uninfected ‘Valencia’ scion, suggesting that scion infection damages roots, regardless of whether they are contaminated or not by CLas. The damage to the root system of IAC3222 was significantly less severe than that of the Swingle rootstock. Multivariate hierarchical analysis considering all evaluated parameters clustered the CLas-infected plants grafted on IAC3222 together with the non-inoculated plants. We concluded that the IAC3222 rootstock was less affected by the CLas-infected scion compared to the Swingle rootstock and is a promising rootstock to minimize the HLB effect on plant development.
Keywords: Candidatus Liberibacter asiaticus; citrus; disease; rootstock